EFEKTIVITAS BUAH KURMA DAN BUAH BIT TERHADAP KADAR HEMOGLOBIN PADA IBU HAMIL TRIMESTER II DI WILAYAH PUSKESMAS KARANGAWEN II KABUPATEN DEMAK - Wening Eka Cahya; Ardhita Listya Fitriani; Fhandy Aldy Mandaty; Rizqitha Rizqitha (LPPM STIKES Muhammadiyah Kendal, 2021)
Pregnant women who suffer from anemia are at risk for miscarriage, premature birth, low birth weight babies, and bleeding before and after childbirth. Data from the Karangawen II Health Center, Demak Regency, the number of pregnant women in 2017 was 910 pregnant women who experienced anemia. In 2018 the number of pregnant women with anemia was 915, in 2019 there were 932 pregnant women with anemia. The purpose of this study was to determine the effectiveness of dates and beets on hemoglobin levels in pregnant women in the second trimester at Karangawen II Public Health Center, Demak Regency. This type of research is a quasi-experimental. The research design used was a two group pre-test-post-test design. The study population was the population of pregnant women in the second trimester at the Karangawen II Public Health Center, Demak Regency who experienced anemia as many as 40 pregnant women. The number of samples of pregnant women in the second trimester at the Karangawen II Health Center Demak was 38 people. The sample was divided into two groups. 18 people of beetroot group and 18 people of dates. The sampling technique in this research is purposive sampling. Results: There are differences in hemoglobin levels of pregnant women in the second trimester at Karangawen II Health Center, Demak Regency before and after being given dates. There are differences in hemoglobin levels of pregnant women in the second trimester in the Karangawen II Public Health Center, Demak Regency before and after being given beets.